TRANSFORMASI PEMBELAJARAN PENDIDIKAN JASMANI DI ERA MERDEKA BELAJAR - Sani; Ega Nurpalah; Erpin Abdalah; Asep Sahrul Gunawan (STKIP Subang, 2026)
The implementation of the Merdeka Belajar policy has brought fundamental changes to learning practices, including physical education. Physical education learning is no longer oriented solely toward mastery of sports techniques, but rather toward the holistic development of students through meaningful, student-centered, and contextual learning experiences. This article aims to examine the transformation of physical education learning in the era of Merdeka Belajar, focusing on changes in learning orientation, instructional strategies, and assessment practices. The study employs a qualitative descriptive approach through literature review of national policies, curriculum documents, and recent scientific articles related to physical education and independent learning. The findings indicate that the transformation of physical education learning emphasizes flexibility in curriculum implementation, the integration of project-based and differentiated learning, and the development of students’ physical literacy, character, and critical thinking skills. Teachers are encouraged to act as facilitators who design adaptive learning environments based on students’ needs, interests, and local contexts. In addition, authentic assessment becomes a key component to evaluate students’ learning processes and outcomes comprehensively. The transformation of physical education learning in the Merdeka Belajar era is expected to improve the quality of learning and foster lifelong healthy and active lifestyles among students.